2013
DOI: 10.4081/ijas.2013.e46
|View full text |Cite
|
Sign up to set email alerts
|

Variability in Candidate Genes Revealed Associations with Meat Traits in the Piemontese Cattle Breed

Abstract: In the last years an increasing number of associations between single nucleotide polymorphisms (SNPs) in candidate genes and production traits have been reported in beef cattle, but very often the results were not validated and few studies considered breeds homozygous for the allele responsible for the muscular hypertrophy. Therefore, we analysed the variability of 19 previously reported SNPs in 12 genes (GH, GHR, GDF8, GHRL, IGF2, LEP, LEPR, MYF5, NPY, POMC, UCP2, UCP3) in the hypertrophic Piemontese breed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…190.6 ± 0.8 a 192.0 ± 0.7 ab 193.0 ± 1.0 b -1.01 ± 0.6 0.2 mated by Lisa et al (2013) in Piedmontese cattle. On the contrary, Chung and Kim (2005) and Zhang et al (2007) reported rather different allele frequencies in Korean cattle in the same SNP (A = 0.33 and G = 0.67) and in 3 Chinese cattle breeds (A = 0.1725 and G = 0.8275 in Nanjang, A = 0.2419 and G = 0.7581 in Qinchone, and A = 0.2477and G = 0.7523 in Jiaxian), respectively.…”
Section: Myf5mentioning
confidence: 96%
“…190.6 ± 0.8 a 192.0 ± 0.7 ab 193.0 ± 1.0 b -1.01 ± 0.6 0.2 mated by Lisa et al (2013) in Piedmontese cattle. On the contrary, Chung and Kim (2005) and Zhang et al (2007) reported rather different allele frequencies in Korean cattle in the same SNP (A = 0.33 and G = 0.67) and in 3 Chinese cattle breeds (A = 0.1725 and G = 0.8275 in Nanjang, A = 0.2419 and G = 0.7581 in Qinchone, and A = 0.2477and G = 0.7523 in Jiaxian), respectively.…”
Section: Myf5mentioning
confidence: 96%